Параметрическая квадратическая стабилизация нелинейных систем с неопределенностью - Хорошун, А.С. (Видавничий дім "Академперіодика" НАН України, 2008)
The notion of parametric quadratic stabilizability (PQ-stabilizability) of nonlinear controlled systems x˙ = [A+deltaA(p)]x+BФ(u) is introduced. The results account for a “shifted equilibrium” in the context of the parametric stability, which is caused by the interplay between reference
inputs and the parameter uncertainty in a system.